Feeding the People, Feeding the Spirit: Revitalizing Northwest Coastal Indian Food - E. N. Anderson (Ethnobiology Letters, 2011)
Review of Feeding the People, Feeding the Spirit:  Revitalizing Northwest Coastal Indian Food. Elise Krohn and Valerie Segrest. 2010. Northwest Indian College, Bellingham, WA.  Pp. x + 158, copiously illustrated, tables, bibliography.